Biosorption of Cr(III), Fe(II), Cu(II), Zn(II) Ions from Liquid Laboratory Chemical Waste by Pleurotus ostreatus - Arbanah, Muhammad; Najwa, M.R. Miradatul; Halim, K.H. Ku (International Journal of Biotechnology for Wellness Industries, 2012)
Heavy metals which present in the liquid laboratory chemical waste should be removed due to their non-biodegradability and toxicity characteristics. However, the conventional treatments in the removal of heavy metals have several limitations. This encourages researchers to introduce alternative treatment methods through biosorption. The process of biosorption is depending on pH, temperature and agitation speed. In the first batch treatment study, synthetic heavy metal solution was introduced prior to the treatment of liquid laboratory chemical waste. The highest biosorption efficiency for Fe(II) and Cu(II) was found to be at pH 6 while Cr(III) at pH 5 while Zn(II) at pH 4. About 80.52% of Fe(II) and 45.20% of Cu(II) was removed at pH 6. The biosorption efficiency of Cr(III) at pH 5 is 12.47% while only 5.04% for Zn(II). The results show that agitation speed of 150 rpm and temperature of 25°C is the best condition for biosorption of heavy metals. Throughout the research, the percentange ’heavy metal’ removal was found to increase with the increasing contact time between Pleurotus ostreatus (P.ostreatus) and liquid laboratory chemical waste. The contact time can rise up to 10 hours. Almost 17.02% of Cr(III), 55.35% of Fe(II), 36.80% of Pb(II), 15.34% of Cu(II) and 13.34% of Zn(II) were removed from chemical waste under suitable treatment conditions. This validates that P.ostreatus is a good biosorbent agent for laboratory chemical waste treatment.